ANALYSIS OF THE TAFSIR CHAPTER IN THE WORK "MUWATTA" (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The "Muwatta" holds a significant position in the development of Hanafi jurisprudence, being equated with the most authoritative works known as "Zahir al-Riwaya". This is due to its provision of substantial evidential support for the Hanafi school. Additionally, it stands as one of the earliest works in the field of comparative jurisprudence. The text exemplifies pure scholarly discourse and contains numerous hadiths advocating for peace and ethical conduct, which are highly pertinent in contemporary times. The "Muwatta" plays a crucial role in enhancing the religious, educational, and socio-spiritual environment.